Transcriptome and co-expression network analyses of key genes and pathways associated with differential abscisic acid accumulation during maize seed maturation - Liangjie Niu; Cui Du; Wenrui Wang; Man Zhang; Wei Wang; Hui Liu; Jinghua Zhang; Xiaolin Wu (BMC Plant Biology, 2022)
Abstract Background Currently, mechanical maize kernel harvesting has not been fully utilized in developing countries including China, partly due to the absence of suitable cultivars capable of rapid desiccation during seed maturation. The initiation of rapid desiccation during seed maturation is regulated by abscisic acid (ABA). For further characterization of ABA-regulated key genes and cellular events, it is necessary to perform transcriptome analysis of maize developing embryos. The ABA synthesis-deficient mutant (vp5) and normal maize (Vp5) seeds are suitable materials for such purpose. Results In the present work, developing vp5 and Vp5 embryos were compared by ABA content and transcriptome analyses. Quantitative analysis revealed the significant difference in ABA synthesis between both genotypes. From 29 days after pollination (DAP), ABA content increased rapidly in Vp5 embryos, but decreased gradually in vp5 embryos. At 36 DAP, ABA level in vp5 decreased to 1/4 that of Vp5, suggesting that the differential ABA levels would affect seed maturation. Comparative transcriptomic analysis has found 1019 differentially expressed genes (DEGs) between both genotypes, with the most DEGs (818) at 36 DAP. Further, weighted correlation network analysis (WGCNA) revealed eight DEGs co-expression modules. Particularly, a module was negatively correlated with ABA content in vp5 embryos. The module was mainly involved in metabolic and cellular processes, and its hub genes encoded thiamine, NPF proteins, calmodulin, metallothionein etc. Moreover, the expression of a set of key genes regulated by ABA was further verified by RT-qPCR. The results of the present work suggested that because of ABA deficiency, the vp5 seeds maintained strong metabolic activities and lacked dormancy initiation during seed maturation. Conclusion Transcriptome and WGCNA analyses revealed significant ABA-related changes in metabolic pathways and DEGs between vp5 and Vp5 during seed maturation. The results would provide insights for elucidating the molecular mechanism of ABA signaling and developing high dehydration tolerance maize suitable for mechanical harvesting.